2020
DOI: 10.1155/2020/3694627
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Patients’ Beliefs and Perception on Medicinal Properties of Natural Hot Spring Bath for Musculoskeletal Problems

Abstract: Natural therapy modalities such as thermal therapy and balneotherapy are commonly being practiced for the management of chronic aches and pain all over the world. Nepal has many such natural hot water springs among which few are famous for therapeutic purposes. Thousands of people with some musculoskeletal problem visit those places in the hope of getting rid of their problems. This study aimed to understand their belief in such therapies, expectations, and satisfaction after treatment along with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Regardless of how hot springs are formed and how they are classified in terms of origin, they offer both medical and biological significance. Medically, hot springs are known to relieve musculoskeletal problems (Vaidya & Nakarmi 2020). Although there is no direct evidence on the medical effectiveness of hot springs, documentation showed a great number of microbial enzymes isolated from these water sources that may explain the partial, although still inconclusive, medicinal effects to the body (Akanbi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of how hot springs are formed and how they are classified in terms of origin, they offer both medical and biological significance. Medically, hot springs are known to relieve musculoskeletal problems (Vaidya & Nakarmi 2020). Although there is no direct evidence on the medical effectiveness of hot springs, documentation showed a great number of microbial enzymes isolated from these water sources that may explain the partial, although still inconclusive, medicinal effects to the body (Akanbi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The environment, density, buoyancy, specific gravity, viscosity, hydrostatic pressure, temperature, and dissolved substances of mineral water will affect balneotherapy. [ 14 ] In vitro tests and clinical studies have shown that certain water-soluble minerals can be absorbed through the skin. Immersion during thermal mineral waters therapy has many physiological effects and causes changes in the neuro-immuno-endocrine system.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective mental status was associated with higher health consciousness, increased hot spa-bathing behavior, and fewer illnesses, while hot spa-bathing behavior was also associated with more illnesses. A report described that most patients suffering from chronic pain believe that hot springs have a healing effect to improve their pain [17] . Therefore, our result may be due to the use of hot spa bathing to alleviate or ameliorate symptoms in the population with diseases.…”
Section: Discussionmentioning
confidence: 99%